The corruption of public officials in times of the coronavirus - Goicochea Elías, José Julio (2020)
The coronavirus pandemic that is currently scourging humanity has managed to take our capacity for surprise to unsuspected limits: on the one hand, we observe through the mass media high- ranking officers of the Peruvian National Police buying products at exorbitant prices that they do not meet quality standards (masks, gloves, etc.) to hand over to their colleagues who valiantly risk their life to take care for ours; to provincial and district mayors making their own stock of basic necessities, and also magistrates who in virtual hearings continue to know processes derived from acts of corruption committed by magistrates who, disregarding Elementary concepts of ethics, took advantage of their position to make a clean sweep of the law and justice. It is worth nothing that the responsibility of these bad servers is aggravated in a superlative way by the disease that has plagued us.